1980
DOI: 10.1111/j.2044-8279.1980.tb02440.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Co‐operative, Competitive, and Individualised Learning Preference Scale for Students

Abstract: Summary. An important variable in the effectiveness of learning is the preference of the student for a mode of learning, i.e., co‐operative, competitive, or individualised. A Learning Preference Scale is therefore an asset, both to teachers as they try to suit the mode of classroom activity to student preferences, and to researchers as they investigate the dynamics of learning, especially aptitude‐treatment interaction. The Learning Preference Scale—Students (LPSS) was developed with a sample of 1,643 Sydney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 0 publications
1
20
0
2
Order By: Relevance
“…However, statistical significance was only observed in five of the seven scales in male students' perceptions (see Table 7): Personalisation, Student Cohesiveness, Task Orientation, Cooperation and Individualisation. This is similar to findings in other research (Johnson & Johnson, 1991;Parker, Rennie, & Harding, 1995;Owens & Straton, 1980). Female students seemed to want less of a decision making role in the classroom.…”
Section: Differences In Perception Based On the Gender Of Studentssupporting
confidence: 90%
See 1 more Smart Citation
“…However, statistical significance was only observed in five of the seven scales in male students' perceptions (see Table 7): Personalisation, Student Cohesiveness, Task Orientation, Cooperation and Individualisation. This is similar to findings in other research (Johnson & Johnson, 1991;Parker, Rennie, & Harding, 1995;Owens & Straton, 1980). Female students seemed to want less of a decision making role in the classroom.…”
Section: Differences In Perception Based On the Gender Of Studentssupporting
confidence: 90%
“…For example, Lira (1995) in his study of secondary school students in Singapore found that male students perceived their classrooms as allowing greater opportunities for working at their own pace and time while female students viewed their classrooms as opportunities to participate and have control of their own learning. Numerous studies also show that learning in science classrooms takes on a competitive nature and, boys prefer competitive and individualised learning, whereas, girls prefer learning which involves cooperative models and mutual assistance (Byrne, Hattie, & Fraser, 1986;Johnson & Johnson, 1991;Owens & Straton, 1980;Parker, Rennie, & Harding, 1995). Johnson and Johnson (1991), however, showed that as students progressed to higher grades both male and female students seemed to gain more interest in competitive learning.…”
mentioning
confidence: 99%
“…This was measured by an abridged form of the Learning Preference Scale-Students (LPSS) (Owens & Straton, 1980). The abridged form consists of three subscales each with the eight items shown by factor analysis to pertain exclusively to competitive (e.g., Trying to be better than others makes me work well), cooperative (e.g., I like to work in a group at school), and individualistic (e.g., I prefer to work by myself so I can go as fast as I like) learning preference respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They too, found gender effects. In a variation on this theme, Owen and Straton [19] were able to show similar preferences to SadlerSmith and Riding [17], which they called co-operative (students working together to achieve a learning goal), competitive (student works alone to compete with other students), and individualistic (students work to achieve their own goals) modes.…”
Section: Teaching Modes Preferencesmentioning
confidence: 88%